Anthropometry and it application in ergonomics - Ciro Romelio Rodriguez-Añez (Universidade Federal de Santa Catarina, 2001)
Anthropometry, is the branch of the human science that studies the physical measurement of the human body, particularly size and shape. Ergonomics is the science of work: of the people who do it and the way it is done; the tools and equipment they use, the places they work in, and the psychological aspects of the working environment. In a simpliﬁ ed way can be understood as the adaptation of work to man. One characteristic of the ergonomic is its interdisciplinarity; since it is based on many different areas of knowledge. Anthropometry has a special importance because of the emergence of complex work systems where knowledge of the physicaldimensions of man with accuracy is important. One application of anthropometrical measurement in ergonomics is the design of working space and the development of industrialized products such as furnishing, cars, tools, etc. With advances in technology, the precision and automation of measurement techniques will increase, improving deﬁnition of human size, and the mechanics of workspaces, clothing and equipment. A well-developed tool will perform better in a worker's hand without injuring his bodily structures. On the other hand, anthropometric data is only meaningful if the workers' activities are also analyzed. RESUMO A antropometria é o ramo das ciências humanas que estuda as medidas do corpo, particularmente o tamanho e a forma. A ergonomia é a ciência do trabalho e envolve: as pessoas que o fazem, a forma como é feito, as ferramentas e equipamentos que elas usam, os lugares em que elas trabalham e os aspectos psicossociais nas situações de trabalho. De forma bastante simpliﬁ cada, pode ser entendida como a adaptação do trabalho ao homem. Uma característica da ergonomia é a sua interdisciplinaridade, pois diversas áreas do conhecimento lhe dão sustentação. A antropometria assumiu uma importância especial com o surgimento dos sistemas complexos de trabalho onde o conhecimento das dimensões físicas do homem com exatidão, é muito importante. Uma das aplicações das medidas antropométricas na ergonomia é no dimensionamento do espaço de trabalho e no desenvolvimento de produtos industrializados como mobília, automóveis, erramentas, etc. Com o avanço da tecnologia, haverá um aumento na precisão e automatização das técnicas de medida para uma melhor deﬁ nição do tamanho humano e da mecânica do espaço de trabalho, roupas e equipamentos. Uma ferramenta bem desenvolvida, terá um desempenho melhor nas mãos de um operador sem prejudicar as estruturas músculo-esqueléticas do mesmo. Por outro lado, os dados antropométricos só têm sentido para a ergonomia se analisadas também as atividades que o trabalhador desenvolve.